RELATIONSHIP BETWEEN GLYCOCALYX COMPONENTS AND MICROALBUMINURIA IN PATIENTS WITH DIABETES MELLITUS - Shanza Rafi; Kamran Shauket; Shazia Naz; Zunairah Hamayun; Nasir Islam; Tayyaba Yasin; Hafsa Yasin; Filza Karim; Rizwana Dilshad (Journal of Population Therapeutics and Clinical Pharmacology, 2024)
Diabetes mellitus is a disease of deregulated blood glucose homeostasis. Microalbuminuria has been described as an early sign of kidney damage. The aim of the study was to determine the association of glycocalyx metabolites with microalbuminuria in type 1 diabetic patients. To determine the association of glycocalyx metabolites with microalbuminuria in diabetic patients. This cross-sectional study was recruited from the 90 patient’s department of Children’s Hospital on the recommendation of a consultant endocrinologist. Patients were designated as having microalbuminuria if they had a 24-h urine measurement >30 mg or an albumin-to-creatinine ratio >30 mg/g albumin-to-creatinine. Total cholesterol, HDL cholesterol, and triglycerides were measured by standard enzymatic methods. Blood and urine samples were obtained from diabetic patients. A probability value of P<0.05 was determined to be statistically significant. The analysis of patient ages indicated a mean age of 12.62±1.73 years. Out of the total of 90 patients, 55 (61.11%) were identified as male, while 35 (38.89%) were identified as female. The Mean albumin to creatinine ration in patients was 356.17±139.24 respectively. The Mean cholesterol level in patients was 182.43±50.89. The mean triglyceride level in patients was 154.17±118.49. Mean HbA1c level in patients was 11.52±1.36. Mean hyaluronic acid level in patients was 283.83±29.51. Hyaluronic acid displayed weak positive correlations with creatinine (r=0.348) and HbA1c levels (r=0.209), and a moderate correlation with the albumin-to-creatinine ratio (r=0.424). A positive significant correlation was observed between hyaluronic acid and ACR. This study suggests that there is a correlation between hyaluronan and ACR in children with T1DM, indicating the importance of monitoring these measures in the management of T1DM.